PEMILIHAN SEKOLAH MENENGAH ATAS/ SEDERAJAT: PERAN LOKASI SEKOLAH DAN KUALITAS SEKOLAH - kartika sari; khusaini khusaini; sri lestari (Journal of Business Education and Social, 2020)
AbstractSchool choice is a process of determining or choosing a higher level secondary school in accordance with its wishes. This study aims to examine the effect of school location, school quality and extracurricular activities on school choice. The population in this study were students of grade 9 SMP Negeri 2 Legok, Tangerang district, totaling 273 students. Sampling was done with a proportionate random sampling technique with a sample size of 163 students. Data collection techniques using online questionnaires (google form) binary logistic regression analysis. The result of the research shows that partially the location of the school, the quality of the school has a significant effect on the probability of students choosing the school they want. As for the extracurricular activity variables did not significantly influence school selection. Simultaneously, it shows the variables of school location, school quality and extracurricular activities simultaneously (together) have a significant effect on school choice.Keywords: Location, Quality, School ChoiceAbstrak